Dietary and socioeconomic risk factors for fumonisin exposure among women of reproductive age in 18 municipalities in Guatemala from 2013 to 2014 - Ariel V. Garsow; Olga R. Torres; Jorge A. Matute; Ronald T. Riley; Julie R. Harris; Archana P. Lamichhane; Orion McCotter; Barbara B. Kowalcyk (Public Library of Science (PLoS), 2022)
Fumonisin exposure is common in populations where maize is a dietary staple, such as in Guatemala, and has been associated with negative health outcomes including neural tube defects. The objective of this study was to estimate fumonisin B1 (FB1) exposure among Guatemalan reproductive-age women and develop a better understanding of the dietary and sociodemographic risk factors for exposure. A cross-sectional study in 18 municipalities in Guatemala was conducted. Midwives and study nurses enrolled consenting women and collected individual and household demographic and socioeconomic data. A food frequency questionnaire was administered to estimate quantity and types of food products consumed. A urine sample was collected and urinary fumonisin B1 (uFB1) concentration was measured. A univariable analysis was conducted to identify predictors of low/high uFB1. Multivariable logistic regression was used to calculate adjusted odds ratios (ORs) and 95% confidence intervals (CIs). In total, 775 women had analyzable urine samples. Higher uFB1 levels were associated with speaking Mayan (OR = 2.33, 95% CI:1.44-3.77), less than high school education (OR = 1.61, 95% CI:1.12-2.30), increasing dietary proportion of maize-based foods (OR = 1.02, 95% CI:1.01-1.03), and consumption of tostadas (fried tortillas) (OR = 1.11, 95% CI:1.02-1.22). Lower uFB1 levels were associated with consumption of highly processed maize-based foods (OR = 0.93, 95% CI:0.87-0.99). Tortillas were the most frequently consumed maize-based food among study participants and significantly associated with high uFB1 exposure in the univariable but not multivariable analysis. Consumption of >4,750 grams/week of maize-based foods, >5,184 g/week of locally produced maize-based foods, and >110 servings/week of tortillas were also significantly associated with high uFB1 exposure in univariable analysis. Populations with low socioeconomic status/education levels and high consumption of maize-based foods had higher fumonisin exposure. Interventions aimed at reducing the risk of exposure to mycotoxins through maize in Guatemala, including the increased consumption of non-maize-based foods, should be further explored.